Intergroup Forgiveness in the Context of Collective Violence: A Measurement Proposal - Castro-Abril, Pablo Enrique (2025)
This study reviewed published measures of intergroup forgiveness used in contexts of violent conflict and subsequently proposed a scale with an integrative model. First, a systematic search (Scopus, Web of Science, PsyINFO) was conducted, identifying 12 scales with 46 items in 121 scientific articles. Second, through expert judgment (K = 0.926) and confirmatory factor analysis (ML) in a sample of 80 university students (72.5% women; M = 21.36 years), four dimensions were validated: Group forgiveness (6 items), Memory (2), Emotions (3), and Victim forgiveness (4). The model showed acceptable fit (CFI = 0.909; RMSEA = 0.097). The results suggest that the proposed scale systematizes the study of intergroup forgiveness, although replication in larger samples is required.